EFEITOS DE DIFERENTES SISTEMAS NANOESTRUTURADOS DE ÓLEOS ESSENCIAIS EM CUPINS SUBTERRÂNEOS (Coptotermes gestroi) - Clerici, Dariane Jornada (2017)
Termites represent a serious threat to the environment, to the agriculture and to the urban environment. Its control is done mainly by the use of chemical pesticides which, alt-hough effective, can cause serious damages to the environment and human beings. An alterna-tive to the use of these pesticides are natural products, such as essential oils with insecticidal action. Although effective, essential oils are unstable, not much soluble in water and degrade by the action of light, oxygen and even moderate temperatures. Thus, the nanostructure of essential oils could solve these problems and make sure they are effective. In this context, the objective of this work was to evaluate for the first time the effects of nanostructures of essen-tial oils on subterranean termites (Coptotermes gestroi). The nanoemulsions of Cymbopogon flexuosus and Eucalyptus globulus presented mean particle diameter of 94.9 and 79.8nm re-spectively, while the mean diameter of the solid lipid nanoparticles of Melaleuca alternifolia was 148.2nm. The value of PDI in all nanostructures was less than 0.3; zeta potential between -8.6 and -8.8 and pH between 4.0 and 5.9. The repellency test revealed that among the nanostructures tested, the solid lipid nanoparticles of M. alternifolia had the highest repellent index (71.6%). Regarding the termite bioassay, there was no significant difference among any of the groups tested in relation to wood consumption. When we evaluated the mortality of the termite mortality, there was a significant difference between control group (wood without treatment) and the wood treated with the solid lipid nanoparticles of M. alternifolia. In the scale of the American Association of Protection to Wood, the rate of the control group was 4 (very severe attack) and of the group treated by the nanoparticles was 9 (light attack). The present study showed that the nanostructure of essential oils with potential insecticidal action may represent a promising tool in fighting termites.